Robotic pylorus-preserving pancreaticoduodenectomy: Technical considerations. (September 2015) - Parisi, Amilcare; Desiderio, Jacopo; Trastulli, Stefano; Cirocchi, Roberto; Renzi, Caudio; Boselli, Carlo; De Santis, Francesco; Petrina, Adolfo; Annecchiarico, Mario; Di Marino, Michele; Bencini, Lapo; Perna, Federico; et al.
Abstract: Laparoscopy has revolutionized the way of thinking abdominal surgery, however, to date there are still limitations making it difficult to apply this technique to some types of surgical procedures considered technically demanding even when performed by open surgery, such as the pancreaticoduodenectomy. This technical note provides a complete description of the surgical procedure performed for the execution of a robotic pancreaticoduodenectomy through the use of the "Da Vinci Si" robotic system. Robotic systems represent a real evolution in minimally invasive surgery. We wish to emphasize this concept, highlighting the application of this technology to complex procedures in digestive surgery.